Neurobehavioural approach to enhance human literacy for character development in creative communication - Hartati, Rita (Politeknik Negeri Bali, 2024)
In recent years, the intersection of neurobehavioral science and human literacy has garnered significant attention, particularly concerning its potential to enhance character development through creative communication. This study aims to investigate how neurobehavioral strategies can be employed to enhance literacy and character development. This research uses a qualitative and quantitative mix method with a neurobehavior approach. In producing products, this research also uses Research and Development (R&D). The research instrument uses a Google form. This research involved 100 students of English Literature Study Program at UNIMED who took the Creative and Innovative Communication course. Firs finding, students predominantly answered ‘agree’ that environmental, socio-economic, media and technology, academic, and leadership factors influence student character development. Second finding, students were able to answer correctly regarding neurobehavior literacy towards character development so that students' character significantly improved and was reflected in their creative communication. Environmental, socio-economic, media and technology, academic, and leadership factors have a big impact on character development. Therefore, based on the neurobehavior approach, we need to have a variety of literacy that supports positive character and experiences. This research will continue regarding how our brains have an impact on increasing creative communication and developing Emotional intelligence with other innovative approaches.